Vliyanie sulodeksida na funktsional'noe sostoyanie endoteliya u bol'nykh s sakharnym diabetom i diabeticheskoyretinopatiey - Natalya Alexandrovna Gavrilova; Olga Evgen'evna Tishchenko (Сахарный диабет)
Aim. To study effect of sulodexide (Vessel Due F) on the functional state of endothelium in patients with diabetic retinopathy. Materials and methods. A total of 37 patients with DR were divided in 2 groups and treated with sulodexide. Group 1 comprised 16 patients withnon-proliferative DR, group 2 included 21 patients with preproliferative DR. The functional state of endothelium was estimated from the plasma andserum levels of endothelial factors (sVCAM, endothelin, nitric oxide, t-PA, Willebrand factor). Results. The measurement of the initial levels of endothelial factors in both groups revealed significant changes in endothelin, nitric oxide, and sVCAMsuggesting disturbances of endothelial function due to DR. Sulodexide therapy normalized it regardless of DR stage and thereby improved functionalactivity of retina. Conclusion. This study has demonstrated beneficial effect of sulodexide on endothelial function in patients with DR due to correction of the productionof vasoactive factors (endothelin, nitric oxide) and stimulation of fibrinolytic activity of the vascular wall (t-PA).